Hegemony Of Javanese Political Culture In Regional Head Elections - Agus Hiplunudin (Sean Institute, 2024)
As for this paper, it reviews the theory of hegemony and political culture. In this case, the Javanese tribe is the main theme. Given that the Javanese tribe is a fairly unique tribe - because of their large number - it is even more interesting if it is connected to the Regional Head Election (Pilkada). There are a number of reasons why ethnic issues are more likely to arise in regional elections compared to national elections such as legislative and presidential elections. First, candidate battles in Pilkada are generally local. Many candidates are running to represent certain groups. This causes candidates who happen to come from or are supported by the majority group to use ethnic issues and sentiments to gain support from voters. This is different from elections at the national level where candidates who run actually want to be perceived as accepted by all groups or groups. Second, the issues raised in local elections are generally local in nature, while issues in national elections are generally general issues such as education, foreign relations, and so on. Candidates running in national elections (such as presidential elections) do not talk about specific conditions in a region, but rather about programs and efforts that will be made to overcome national problems.